Clinical features and outcomes of pregnancy-related acute aortic dissection - Braverman, Alan C.; Mittauer, Eric; Harris, Kevin M.; Evangelista, Arturo; Pyeritz, Reed E.; Brinster, Derek; Conklin, Lori; Suzuki, Toru; Fanola, Christina; Ouzounian, Maral; Chen, Edward; Myrmel, Truls; et al. (JAMA cardiology, 2021)
Women with aortopathy conditions are at risk for pregnancy-related aortic dissection, and these conditions may not be recognized until after the aortic dissection occurs.To examine the clinical characteristics, imaging features, and outcomes in women with pregnancy-related acute aortic dissection.A cohort study, comprising data from the International Registry of Acute Aortic Dissection (IRAD) (February 1, 1998, to February 28, 2018). The multicenter referral center study included 29 women with aortic dissection during pregnancy or less than 12 weeks post partum in IRAD from 1998 to 2018.Clinical features of pregnancy-related aortic dissection to be studied included underlying aortopathy, aortic size, type of aortic dissection, timing of dissection, hypertension, and previous aortic surgery.A total of 29 women (mean [SD] age, 32 [6] years) had pregnancy-related aortic dissection, representing 0.3% of all aortic dissections and 1% of aortic dissection in women in the IRAD. Among women younger than 35 years, aortic dissection was related to pregnancy in 20 of 105 women (19%). Thirteen women (45%) had type A aortic dissection, and 16 women (55%) had type B. Aortic dissection onset was known in 27 women (93%): 15 during pregnancy, 4 in the first trimester, and 11 in the third trimester; 12 were post partum, occurring a mean (SD) of 12.5 (14) days post partum. At type A aortic dissection diagnosis, the mean (SD) aortic diameters were sinus of Valsalva, 54.5 (5) mm and ascending aorta, 54.7 (6) mm. At type B aortic dissection diagnosis, the mean (SD) descending aortic diameter was 32.5 (5) mm. Twenty women (69%) had an aortopathy condition or a positive family history: 13 women (65%) with Marfan syndrome, 2 women (10%) with Loeys-Dietz syndrome, 2 women (10%) with bicuspid aortic valves, 2 women (10%) with a family history of aortic disease, and 1 woman (5%) with familial thoracic aortic aneurysm. Aortopathy was not recognized until after aortic dissection in 47% of the women. Twenty-eight women (97%) survived aortic dissection hospitalization.Aortic dissection complicating pregnancy is rare. Most pregnancy-related aortic dissection is due to an aortopathy often not diagnosed until after aortic dissection. In this study, type A aortic dissections were associated with a dilated aorta, and type B aortic dissections often were not. Recognition of underlying conditions and risks for aortic dissection may improve management of pregnancy in women with aortopathy.
"Published online: October 14, 2020".- Artikel-Frontdoor
Gesehen am 09.09.2024